Influence of zinc nanoaquacitrate on the immuno-physiological reactivity and productivity of the organism of rabbits - О. V. Boiko; О. F. Honchar; Y. V. Lesyk; І. І. Kovalchuk; B. V. Gutyj (Regulatory Mechanisms in Biosystems, 2020)
Zinc is necessary for maintaining the immune status, and its deficiency in the organisms of animals is usually accompanied by the condition of immune deficiency. The objective of the study was determining the effect of different amounts of zinc on the immune-biological reactivity and productivity of the organism of rabbits after their weaning on the 50th and 86th days of life. For the study, rabbits with the weight of 1.2–1.4 kg were selected and divided into four groups (control and three experimental). The rabbits of the control group were fed with unlimited balanced granulated compound feed, and had free access to water. The animals of the I, II and III experimental groups were watered with zinc nanoaquacitrate in the amounts of 0.25, 0.50 and 0.75 mg of Zn/kg of body weight. Compared with the control group, watering of the animals of the experimental groups with zinc nanoaquacitrate to a greater extent affected the content of phagocytic activity, lysozymic and bactericidal activities of the blood serum as integral factors of non-specific cellular and humoral resistance of the organism, which manifested in the increase in their content in blood on the 12th, 24th and 36th days of the experiment. Use of organic supplement in the diet of rabbits had a stimulating effect on the functioning of the immune system of their organism, which was seen in the higher content of total immunoglobulins, sialic acids and ceruloplasmin in the blood of animals watered with zinc nanoaquacitrate in the quantities of 0.50 and 0.75 mg of Zn/kg of body weight on the 24th and 36th days of the experiment. Use of organic compound of zinc in the diet caused high parameters of growth of the organism of rabbits during the period of 36 days, which manifested in the highest parameters of average-day increments and body weight on the 86th day of the life of the rabbits from the III experimental group, which received zinc nanoaquacitrate in the amounts of 0.75 mg of Zn/kg of body weight compared with the control group. Watering rabbits with zinc nanoaquacitrate during the study was accompanied by probable changes in the number of erythrocytes, concentration of hemoglobin and erythrocyte indices, which could indicate a positive effect of the employed additives on the hematopoietic function of the rabbits’ organism. The data of the performed experiment suggest that watering with larger amounts of organic compound of zinc has a positive effect on the processes of formation of immuno-physiological reactivity of the rabbits’ organism and increase in their productivity. The practical purpose is the study of the impact of watering with zinc nanoaquacitrate on the immuno-biological reactivity of the organism of rabbit dams during the period of lactation.